ECOLOGICAL ANALYSIS OF THE PHYTOCHEMICALS IN FLOWERS AND LEAVES OF Calotropis procera (R. Br.) IN SOME STATES OF NIGERIA - LAKWANNUM, G. Y.; K. S. OLORUNMAIYE; AJIYA B.C.; AHMAD, MUHAMMAD; BAKO, S. P. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Calotropis procera plant is popularly known because it produces large quantity of thick white milky juice when cut or break. Plant derived substances have obtained greater attention in the recent years which are used to prevent and cure human diseases as they are considered to be more bio friendly worldwide. An ecological study has been carried out on Comparative analysis of the phytochemicals C. procera, between Ilorin and Gombe metropolises. Some matured freshly parts flower and leaves of the plant were randomly collected from the two metropolises, the collected parts were dried under shade and was pulverised into coarse powder using mortar and pestle. Each powdered plant parts were extracted using water, methanol and ethanol as extractants. The crude extracts of flowers and leaves was screened for the phytochemicals, which revealed the presences of the following phytochemical, saponins, tannin, alkaloids, flavonoids, steroids, terpenoids, and glycosides in both plant parts with variations. The phytochemicals are moderately correlated and statistically significant at (α = 0.05) and (α = 0.01). Also, when the phytochemicals were compered between the two metropolises. The results shows were significantly difference at (α = 0.05). For the flowers, and leaves (0.850, 0.080) between the two metropolises respectively. The variation observed in the occurrence of the phytochemical in studied parts between the two metropolises may be attributed to the age of the plant, solubility of the solvents into solution of specific type and soil types in the study area. The ethno botanical information collected on the uses of C. procera revealed that the plant is commonly used in making local cheese (wara) as food, its medicinal, firewood, and as fodder for animals.